Amaranth Protein Hydrolysates Efficiently Reduce Systolic Blood Pressure in Spontaneously Hypertensive Rats - Ramírez-Torres, Giovanni (Molecules, 2017)
Alcalase is the enzyme of choice to release antihypertensive peptides from amaranth proteins, but the hydrolysis conditions have not been optimized yet. Furthermore, in vivo assays are needed to confirm such a hypotensive effect. Our aim was to optimize the hydrolysis of amaranth protein with alcalase and to test in vivo the hypotensive effect of the hydrolysates. A response surface analysis was carried out to optimize the hydrolysis reaction. The response variable was the Angiotensin Converting Enzyme (ACE-I) inhibition. The hydrolysis degree was determined (free alpha-amino groups measurement). The optimized hydrolysate bioavailability was assessed in the sera of mice and the hypotensive effect was assessed in spontaneously hypertensive rats. Control groups were administered captopril or water. The optimized hydrolysis conditions were: pH = 7.01, temperature = 52 °C, enzyme concentration 0.04 mU/mg, and time = 6.16 h. The optimized hydrolysate showed a 93.5% of ACE-I inhibition and a hydrolysis degree of 74.77%. After supplementation, the hydrolysate was bioavailable in mice from 5 to 60 min, and the hypotensive effect started at 4 h in spontaneously hypertensive rats (p < 0.05 vs. water group). This effect was similar to the captopril hypotensive effect for the next 3 h (p > 0.05). The use of amaranth-optimized hydrolysates as hypotensive supplements or ingredient for functional foods seems feasible.